Alloying behavior, microstructure and mechanical properties in a FeNiCrCo0.3Al0.7 high entropy alloy - Chen, Weiping; Fu, Zhiqiang; Fang, Sicong; Xiao, Huaqiang; Zhu, Dezhi (Materials in engineering, 2013)
•FeNiCrCo0.3Al0.7 high entropy alloy is prepared via MA and SPS.•Two BCC phases and one FCC phase were obtained after SPS.•The two BCC phases are enriched in Fe–Cr (A2 structure) and enriched in Ni–Al (B2 structure).•Bulk FeNiCrCo0.3Al0.7 HEA exhibits excellent mechanical properties. The present paper reports the synthesis of FeNiCrCo0.3Al0.7 high entropy alloy (HEA) by mechanical alloying (MA) and spark plasma sintering (SPS) process. Alloying behavior, microstructure, mechanical properties and detailed phases of the alloy were investigated systematically. During MA, the formation of a supersaturated solid solution with body-centered cubic (BCC) structure occurred. However, partial BCC structure phase transformed into a face-center cubic (FCC) structure phase during SPS. Two BCC phases with nearly the same lattice parameter of 3.01Å and one FCC phase with the lattice parameter of 3.72Å were characterized in the transmission electron microscope (TEM) images. The two BCC phases which are evidently deviated from the definition of high entropy alloys (HEAs) are enriched in Fe–Cr and enriched in Ni–Al, respectively. Moreover, the FCC phase agrees well with the definition of HEAs. Bulk FeNiCrCo0.3Al0.7 alloy with little porosity exhibits much better mechanical properties except compression ratio compared with other typical HEAs of FeNiCrCoAl HEA system. The yield strength, compressive strength, compression ratio and Vickers hardness of FeNiCrCo0.3Al0.7 alloy are 2033±41MPa, 2635±55MPa, 8.12±0.51% and 624±26Hv, respectively. The fracture mechanism of bulk FeNiCrCo0.3Al0.7 alloy is dominated by intercrystalline fracture and quasi-cleavage fracture.